How to honeymoon alone eaudiobook - Hayle, Olivia (Olivia Hayle, 2023)
A paradise island. Two strangers. The attraction they never saw coming... When Eden dumped her cheating ex before the wedding, the last thing she expected was to go on their tropical honeymoon alone. But with no refunds possible, she packs her budget guidebook and broken heart, and sets off. She plans to relax on the beach, swim in the ocean, and drink cocktails until she feels like herself again... or falls over. Whichever comes first. What she's not expecting is the brusque, handsome stranger who sits down at her table on the first night. Philip Meyer is a grumpy workaholic, and so irritatingly cynical that it makes her forget she's grieving just to prove him wrong about the world. The two have nothing in common... except trying to forget who they've left behind. The luxury resort isn't too big, and fate soon pushes them together again. And again. Catamaran cruises and midnight swims give way to late night room service and whispered nothings. Maybe opposites really do attract. But every vacation has to end, even the very best ones... Can these two opposites make it last?